2004
DOI: 10.1002/yea.1128
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and post‐translational regulation of neutral trehalase in Schizosaccharomyces pombe during thermal stress

Abstract: In the fission yeast Schizosaccharomyces pombe, a heat shock enhances transcription of the ntp1 + gene, encoding the hydrolytic enzyme neutral trehalase. As compared to wild-type cells, cells devoid of the MAP kinase Sty1p showed a strong decrease in ntp1 + expression induced by the temperature upshift, indicating that the stressactivated protein kinase (SAPK) pathway regulates the expression of this gene during heat shock. The transcription factor Atf1p, which is the main downstream target for Sty1p in the SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Pap1 accumulates in the nucleus in a stress-and Spc1-dependent manner and is required for survival under low levels of oxidative stress (25,28,36). Although the precise mechanisms by which Spc1 activates Atf1 or Pap1 dependent transcription are unclear, a number of target stress response genes have now been identified which are dependent on Spc1, Atf1, or Pap1 (2,27,30,35,44,45).…”
mentioning
confidence: 99%
“…Pap1 accumulates in the nucleus in a stress-and Spc1-dependent manner and is required for survival under low levels of oxidative stress (25,28,36). Although the precise mechanisms by which Spc1 activates Atf1 or Pap1 dependent transcription are unclear, a number of target stress response genes have now been identified which are dependent on Spc1, Atf1, or Pap1 (2,27,30,35,44,45).…”
mentioning
confidence: 99%
“…Atf1 and/or Pcr1 are key responders/effectors of many other signals, including those induced by osmolarity, oxidative state, heavy metals, abundance of nutrients, carbon source, DNA damage and chronological aging (42,47,51,54,60,(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80). These multiple, diverse signals-like those generated by differences in temperature-probably impinge upon Atf1 and Pcr1 to control rates of recombination at M26-class hotspots in the genome.…”
Section: A Model For Environmentally and Metabolically Induced Plastimentioning
confidence: 99%
“…Generally in yeast, the regulation of trehalose synthesis and breakdown is done by cAMP-dependent phosphorylation mechanisms ( 24 ). It has been reported that the ntp1 + expression is regulated by the pathway of protein kinase cascade activated under osmotic or oxidative stress ( 23 , 25 ) or by the binding of the transcription factors to elements such as cAMP-response element under thermal stress ( 26 ). In the present study, ird5 and ird11 were used to evaluate whether or not trehalose contributes to survival under moderate oxidative stress.…”
Section: Introductionmentioning
confidence: 99%